2020
DOI: 10.1103/physrevb.101.125131
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics in a Hubbard dimer coupled to fermionic baths: Phenomenological description and its microscopic foundation

Abstract: We study relaxation dynamics in a strongly-interacting two-site Fermi-Hubbard model that is induced by fermionic baths. To derive the proper form of the Lindblad operators that enter an effective description of the system-bath coupling in different temperature regimes, we employ a diagrammatic real-time technique for the reduced density matrix. An improvement on the commonly-used secular approximation, referred to as coherent approximation, is presented. We analyze the spectrum of relaxation rates and identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…Unlike the common secular approximation [75,76], this approximation retains nontrivial effects due to the coupling of coherence and population dynamics, i.e., off-diagonal elements of ρ in the local energy eigenbasis couple to diagonal elements, see also Ref. [80]. Moreover, unlike, e.g., the Wangsness-Bloch-Redfield approximation [71,72,81], this scheme is guaranteed to yield completely positive trace-preserving (CPTP) dynamics [73,74]-an essential requirement for a physical, probabilistic interpretation of the reduced density matrix ρ(t ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the common secular approximation [75,76], this approximation retains nontrivial effects due to the coupling of coherence and population dynamics, i.e., off-diagonal elements of ρ in the local energy eigenbasis couple to diagonal elements, see also Ref. [80]. Moreover, unlike, e.g., the Wangsness-Bloch-Redfield approximation [71,72,81], this scheme is guaranteed to yield completely positive trace-preserving (CPTP) dynamics [73,74]-an essential requirement for a physical, probabilistic interpretation of the reduced density matrix ρ(t ).…”
Section: Introductionmentioning
confidence: 99%
“…But such negative eigenvalues will be quite close to zero, and can be shown to be below accuracy level of the Redfield equation [39,45,47,54]. Several more-refined Lindblad equations have been proposed to circumvent these drawbacks [55][56][57][58][59][60]. Nevertheless, it has been shown that all of these approaches have inherent limitations even to the leading order in the system-bath coupling strength when describing a system coupled to multiple thermal baths [45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel approach termed PERLind (position and energy resolved Lindblad equation) was introduced [29] in an attempt to interpolate between the local and global approach. Since then, multiple microscopic derivations were given [30][31][32][33], showing that the PERLind approach does not require any additional assumptions going beyond the ones already present when performing Born-Markov approximations. Compared to the global and local approaches, the PERLind approach thus has an increased regime of validity, making it a very promising approach.…”
Section: Introductionmentioning
confidence: 99%